Malaysian’s concern toward Rohingya / Nur Hamizah Balqish Muhamad…[et.al] - Muhamad, Nur Hamizah Balqish; Hamdan, Aisyah Maisarah; Muhammad Yatim, Muhammad Firdaus; Ridzuan, Abdul Rauf (Faculty of Communication & Media Studies, 2019)
This study is done in order to find the level of concern towards Rohingya in Malaysia. This study also used social capital theory as foundations theories for model development. The minimum sample size was determined through G⃰Power analysis. The study involved 244 respondents, selected through a cluster sampling technique involving three main ethnics in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables were measured through scales previously used by other researchers. SPSSS ver. 20 software was used in the analysis. Results of the SPSS indicated that the level of concern, for all four factors namely religion, helpless, and humanity show very high level.